2006
DOI: 10.1016/j.otohns.2006.03.043
|View full text |Cite
|
Sign up to set email alerts
|

Frontal sinus fractures: A 28‐year retrospective review

Abstract: The etiology and severity of FSF has changed from 1974 to 2002. This is reflected in a reduced number of fractures resulting from MVAs as well as a reduced severity of injury. The most likely explanation is the use of safety belts and airbags.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 5 publications
2
51
0
7
Order By: Relevance
“…Generally, fractures of the frontal bone are associated with high impact trauma and dynamic forces, such as traffic accidents, assaults, and sport accidents (May, 1970; Tiwari et al, 2005; Bell et al, 2007; Mithani et al, 2009). The injuries of the frontal region are varying, as they range from isolated fractures of the anterior sinus' wall, to very complex fractures involving the orbit and skull base (Strong et al, 2006; Holier et al, 2010; Dimitrijevic et al, 2014). Fracture pattern and its complexity depend on many factors, such as impact force intensity and direction, site of impact, and frontal bone quality.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, fractures of the frontal bone are associated with high impact trauma and dynamic forces, such as traffic accidents, assaults, and sport accidents (May, 1970; Tiwari et al, 2005; Bell et al, 2007; Mithani et al, 2009). The injuries of the frontal region are varying, as they range from isolated fractures of the anterior sinus' wall, to very complex fractures involving the orbit and skull base (Strong et al, 2006; Holier et al, 2010; Dimitrijevic et al, 2014). Fracture pattern and its complexity depend on many factors, such as impact force intensity and direction, site of impact, and frontal bone quality.…”
Section: Introductionmentioning
confidence: 99%
“…The authors do not speculate as to the etiology of the frontalis weakness; they only conclude that cranialization may not be appropriate for minimally displaced posterior table fractures based on noninferior outcomes in similar patients who were managed nonoperatively. A second retrospective review by Strong et al analyzed 130 patients who were treated surgically for frontal sinus fracture over 15 years and found that 5 patients (4%) suffered from temporal nerve paresis postoperatively [1]. Unfortunately, no information was given on the severity of the fracture, the type of surgery, or the timing of the complication.…”
Section: Discussionmentioning
confidence: 99%
“…Frontal sinus fractures (FSF) are relatively uncommon and can be associated with significant morbidity [1]. Etiologies of FSF include high-energy, blunt traumatic events such as motorcycle accidents, automobile accidents, and interpersonal violence and are often associated with multiple concomitant injuries [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Consequently, frontal sinus fractures account for only 5 to 15% of maxillofacial injuries and are most commonly associated with motor vehicles accidents, sporting events, and assaults. 4 The extreme force required to fracture the anterior table of the frontal sinus results in serious associated injuries in many patients. 5 Sixty-six percent of patients will have associated facial fractures.…”
Section: Epidemiologymentioning
confidence: 99%